Application of the Waiting Line Method for Evaluation of the IAIN Batusangkar Information Technology Helpdesk Information System (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Information Technology and Database (TIPD) IAIN Batusangkar is a unit engaged in the field of IT services, namely software and network maintenance software application services so that students / lecturers / units have to go to the TIPD office and fill out a complaint form after which repairs are made by officers or staff TIPD, because the procedures and services provided took a long time so that the TIPD IT services at IAIN Batusangkar had not been able to provide maximum service. This study aims to produce a system that can facilitate TIPD IT services by using a helpdesk information system with the waiting line method. This type of research is the collection of library research data through field research (Field Research), library research, laboratory research, system analysis, application design and application testing. Data collection techniques in this study were using interviews and collecting documents. The results showed the helpdesk application that was built to provide convenience to TIPD IT services and can improve the performance of TIPD officers. Each service with the waiting line method, the technician service facility level has a busy 37% level from the previous 61%, the expected time for each customer arrival to wait on the Waiting Line is 0.21 minutes from the previous one, 1.8 minutes, and time Expected by each customer arrival while in the system or waiting in service is 3.6 minutes from the previous 7.2 minutes, with this it can be said that the helpdesk information system application can provide maximum service.